Loss-on-ignition (LOI) data for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Anna Plikk; Stefan Engels; Maria Fernández-Fernández; Christos Katrantsiotis; Malin E Kylander; Ludvig Löwemark; Sakari Salonen; Minna Väliranta; Karin Helmens (PANGAEA, 2025)
This dataset provides Loss-on-ignition (LOI) data for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. LOI values (%) are presented against both depth (m) and age (ka BP). The LOI dataset was used to provide information on Eemian landscape dynamics at Sokli (Plikk et al., 2016). A total of 112 samples were analyzed for LOI. Subsamples of 1 cm3 were dried in a 105 °C oven for 24 hrs before being placed in a furnace at 550 °C for 4 hrs and at 950 °C for 1 hour. Loss-on-ignition was calculated by comparing the dry weight of the samples before and after combustion at 550 °C following Heiri et al. (2001) and results are expressed as a percentage. The analyses were performed in the laboratories of Stockholm University, Sweden.